Co-translational mechanisms of protein maturation - Gloge, Felix; Becker, Annemarie; Kramer, Günter; Bukau, Bernd (Current opinion in structural biology, 2014)
Protein biogenesis integrates multiple finely regulated mechanisms, ensuring nascent polypeptide chains are correctly enzymatically processed, targeted to membranes and folded to native structure. Recent studies show that the cellular translation machinery serves as hub that coordinates the maturation events in space and time at various levels. The ribosome itself serves as docking site for a multitude of nascent chain-interacting factors. The movement of ribosomes along open reading frames is non-uniformous and includes pausing sites, which facilitates nascent chain folding and perhaps factor engagement. Here we summarize current knowledge and discuss emerging concepts underlying the critical interplay between translation and protein maturation in E. coli.
Available online 12th December 2013
Gesehen am 25.09.2020